2004
DOI: 10.1038/sj.cdd.4401467
|View full text |Cite
|
Sign up to set email alerts
|

A role for Id in the regulation of TGF-β-induced epithelial–mesenchymal transdifferentiation

Abstract: Epithelial-mesenchymal transdifferentiation (EMT) is a critical morphogenic event that occurs during embryonic development and during the progression of various epithelial tumors. EMT can be induced by transforming growth factor (TGF)-b in mouse NMuMG mammary epithelial cells. Here, we demonstrate a central role of helix-loop-helix factors, E2A and inhibitor of differentiation (Id) proteins, in TGF-b-induced EMT. Epithelial cells ectopically expressing E2A adopt a fibroblastic phenotype and acquire migratory/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(137 citation statements)
references
References 43 publications
7
127
2
1
Order By: Relevance
“…TGF-␤ has been reported to induce EMT in NMuMG cells (Miettinen et al, 1994;Piek et al, 1999;Kondo et al, 2004). As previously reported, treatment with TGF-␤ dramatically altered the morphological phenotypes of NMuMG cells from cobblestone-like to spindle shapes ( Figure 1A).…”
Section: Tgf-␤ Promotes Emtsupporting
confidence: 74%
See 3 more Smart Citations
“…TGF-␤ has been reported to induce EMT in NMuMG cells (Miettinen et al, 1994;Piek et al, 1999;Kondo et al, 2004). As previously reported, treatment with TGF-␤ dramatically altered the morphological phenotypes of NMuMG cells from cobblestone-like to spindle shapes ( Figure 1A).…”
Section: Tgf-␤ Promotes Emtsupporting
confidence: 74%
“…Expression of Twist could not be detected, whereas that of E12/E47 was not altered after TGF-␤ treatment (data not shown and Kondo et al, 2004). Expression of mRNA for Id2, a negative regulator of TGF-␤-induced EMT (Kondo et al, 2004;Kowanetz et al, 2004), decreased rapidly by 4 h after treatment with TGF-␤ ( Figure 1D). These findings demonstrated that, among these factors, increases in SIP1 and ␦EF1 by TGF-␤ appear to strongly correlate with the reduction in E-cadherin in NMuMG cells.…”
Section: Tgf-␤ Promotes Emtmentioning
confidence: 86%
See 2 more Smart Citations
“…Although still preliminary, the evidence available suggests that components of the PAR polarity complex are not direct targets of EMT transcriptional regulators, but rather they can be modulated in response to different oncogenes, tumour suppressors or EMT regulatory signals (reviewed by Lee and Vasioukhin, 2008). TGF-b is one of the more robust cues inducing EMT in different model systems (reviewed by Zavadil and Bottinger, 2005), leading to the upregulation of several EMT inducers, including SNAI1/SNAI2, ZEB1, Twist and the Id factors through Smad-dependent and Smad-independent pathways (Peinado et al, 2003;Kondo et al, 2004;Thuault et al, 2006;Moustakas and Heldin, 2007). Recent insights into the regulation of cell polarity by TGF-b during EMT have converged on the PAR complex.…”
Section: Regulation Of Cell Polarity Genes During Emtmentioning
confidence: 99%